Relationship of nurse therapeutic communication to inpatient satisfaction - Rahagia, Rasi; Nurhanifah, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Patient satisfaction is a key indicator of healthcare service quality. One of the most influential factors in determining patient satisfaction is the quality of communication between nurses and patients. As a purposeful and goal-oriented interaction, therapeutic communication plays a critical role in building trust, reducing anxiety, and improving patient outcomes. This study analyzes the relationship between nurse therapeutic communication and inpatient satisfaction in a hospital setting. Research Methodology: This research used a quantitative, cross-sectional design. Data were collected through questionnaires distributed to 120 inpatients across medical and surgical wards in a general hospital. The instrument measured nurse therapeutic communication using a standardized scale and patient satisfaction using a validated satisfaction questionnaire. The data were analyzed using the Pearson correlation test and multiple linear regression to determine the strength and significance of the relationship. Result: The study found a significant positive correlation between nurse therapeutic communication and inpatient satisfaction (r = 0.68, p < 0.001). Regression analysis showed that therapeutic communication contributed to 46% of the variance in patient satisfaction (RÂ² = 0.46). Empathy and active listening were the strongest predictors of patient satisfaction among the dimensions of therapeutic communication. Conclusion: Therapeutic communication by nurses has a strong and significant relationship with inpatient satisfaction. Enhancing nursesâ€™ skills in empathetic interaction, active listening, and clear communication may improve overall patient experiences and satisfaction levels.